Artificial intelligence based hybridization for economic power dispatch - Samala, Rajesh (Cognitive Robotics, 2023)
Revenue loss is a major issue for any country. Conversion of this loss into utilization would prove to be a huge benefit to the country. In view of this fact, the economic load dispatch problem draws much attention. Substantial reduction in fuel cost could be obtained by the application of modern heuristic optimization techniques for scheduling of the committed generator units. In this study, two cases are taken named three-unit system and six-unit system. The fuel cost for both systems compared using conventional lambda-iteration method and PSO method. These calculations are done for without transmission loss as well as with transmission losses. In the end, the fuel cost for both methods compared to analyze the better one from them. All the analyses are executed in MATLAB environment
uGDX
Keywords: Economic power dispatch ALO FLC